Making secret sharing based cloud storage usable. (9th October 2019) - Framner, Erik; Fischer-Hübner, Simone; Lorünser, Thomas; Alaqra, Ala Sarah; Pettersson, John Sören
Abstract : Purpose: The purpose of this paper is to develop a usable configuration management for Archistar, which utilizes secret sharing for redundantly storing data over multiple independent storage clouds in a secure and privacy-friendly manner. Selecting the optimal secret sharing parameters, cloud storage servers and other settings for securely storing the secret data shares, while meeting all of end user's requirements and other restrictions, is a complex task. In particular, complex trade-offs between different protection goals and legal privacy requirements need to be made. Design/methodology/approach: A human-centered design approach with structured interviews and cognitive walkthroughs of user interface mockups with system administrators and other technically skilled users was used. Findings: Even technically skilled users have difficulties to adequately select secret sharing parameters and other configuration settings for adequately securing the data to be outsourced. Practical implications: Through these automatic settings, not only system administrators but also non-technical users will be able to easily derive suitable configurations. Originality/value: The authors present novel human computer interaction (HCI) guidelines for a usable configuration management, which propose to automatically set configuration parameters and to solve trade-offs based on the type of data to be stored in the cloud. Through these automatic settings, not only system administrators but also non-technical users will be able to easily derive suitable configurations.